PREVENTING THE SPREAD OF HOAXES BY INCREASING DIGITAL LITERACY - Syafruddin Pohan; Yogo Pamungkas L. Tobing; Aldino Mazuda (Sean Institute, 2023)
This article discusses the importance of digital literacy skills in combating the spread of misinformation (hoaxes) in the post-truth era. Digital literacy empowers individuals to have greater control in understanding messages disseminated through digital media. The research conducted for this article adopts a literature review methodology, exploring relevant references, and proposes three categories of digital literacy definitions. The level of digital literacy comprehension influences an individual's ability to navigate and interpret information, particularly within the realm of social media. While social media platforms can enhance engagement in democratic systems, they also carry negative risks associated with freedom of expression. Data from Diskominfo Jabar in 2018 revealed that 92.4% of hoaxes were detected through social media channels. Therefore, digital literacy is crucial in preventing the spread of hoaxes, especially on microblogs (Twitter) and social networking sites (Facebook and Instagram). This article emphasizes the significance of digital literacy in communication and how it can effectively combat misinformation in the post-truth era. The plans to enhance digital literacy as a preventive mechanism are also discussed. Digital literacy skills enable individuals to cognitively verify information and present alternative options to debunked falsehoods. By improving digital literacy, social media users can exert optimal control over their usage and mitigate the proliferation of hoaxes. In confronting the challenges of misinformation in the post-truth era, an effective strategy is to promote digital literacy and educate the public on recognizing hoax characteristics, verifying information, and addressing dubious content.